The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/15533174.2013.831880
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization andIn VitroAntibacterial Activity of Some Novel Metal Complexes With Schiff Base Ligands Derived From Thiosemicarbazide

Abstract: Six novel mononuclear Schiff base metal complexes of the type [ML 1 L 2 ]X and [ML 1 L 2 X], where M D Cu(II), Ni(II), Co(II), Mn(II), Zn(II), and VO(IV) have been synthesized by condensation of 1-(1-(pyridine-2-yl)ethylidene)thiosemicarbazide (L 1 ) and 1-(1-(2,4-dihydroxyphenyl)ethylidene)thiosemicarbazide (L 2 ) in the presence of divalent metal salts. The synthesized ligands and complexes were structurally characterized on the basis of elemental analysis, IR, UV-visible, 1 H NMR spectroscopy, molar conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This may be due to a decrease in hydrogen bonding of -OH groups in C 62 (compared to free ligands) with group of the enzymes of microbes which inhibit the penitration of C 62 to the cell walls. [128] It has been reported that often the activity of a biologically active ligand decreases or completely vanishes after replacement of phenolic protons by a metal ion since the activity of a particular molecule may be due to that phenolic group. [67] An other interesting complex C 63 having molecular structure and coordiantion behaviour similar to C 59 was synthesized using guaifenesin ( a L 63 ) and 2aminoacetic acid ( b L 63 ).…”
Section: Mn-complexes With Mixed Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to a decrease in hydrogen bonding of -OH groups in C 62 (compared to free ligands) with group of the enzymes of microbes which inhibit the penitration of C 62 to the cell walls. [128] It has been reported that often the activity of a biologically active ligand decreases or completely vanishes after replacement of phenolic protons by a metal ion since the activity of a particular molecule may be due to that phenolic group. [67] An other interesting complex C 63 having molecular structure and coordiantion behaviour similar to C 59 was synthesized using guaifenesin ( a L 63 ) and 2aminoacetic acid ( b L 63 ).…”
Section: Mn-complexes With Mixed Ligandsmentioning
confidence: 99%
“…C 62 proved to have lower activity compared to ligands against almost all the tested microbes (Table ). This may be due to a decrease in hydrogen bonding of ‐OH groups in C 62 (compared to free ligands) with group of the enzymes of microbes which inhibit the penitration of C 62 to the cell walls . It has been reported that often the activity of a biologically active ligand decreases or completely vanishes after replacement of phenolic protons by a metal ion since the activity of a particular molecule may be due to that phenolic group .…”
Section: Mn–complexes With Mixed Ligandsmentioning
confidence: 99%
“…On the other hand, the biological activities of metal complexes have gained attention during the last two decades due to their diverse biomedical applications like antibacterial (Osman et al, 2012;Sakthilatha et al, 2015;Wakil et al, 2017), antifungal (Ran et al, 2011El-Tabl et al, 2012), cytotoxicity El-Seidy et al, 2013), antitumor (Chang et al, 2015;Rubino et al, 2016), antiviral (Abou-Melha et al, 2015, DNA cleavage (Kokare et al, 2017;Subbaraj et al, 2014), antimalarial (Hubin et al, 2014, antioxidant (Abdel-Monem et al, 2017;Lakshmi et al, 2011), analgesic and anti-inflammatory (Hoonur et al, 2010; activities. Cisplatin (6), cis-[PtCl 2 (NH 3 ) 2 ], is the most famous and the best-known example of a small molecule-metal complex that has been used in the chemotherapy for various cancer diseases (Ott and Gust, 2007).…”
Section: Introductionmentioning
confidence: 99%